High-Nb hawaiite–mugearite and high-Mg calc-alkaline lavas from northeastern Iran: Oligo-Miocene melts from modified mantle wedge. Issue 2 (22nd January 2019) - Ahmadi, Parham; Ghorbani, Mohammad Reza; Coltorti, Massimo; Kuritani, Takeshi; Cai, Yue; Fioretti, Anna Maria; Braschi, Eleonora; Giacomoni, Pier Paolo; Aghabazaz, Farzaneh; Babazadeh, Shahrouz; Conticelli, Sandro
ABSTRACT: Tertiary volcanic rocks in northwestern Firoozeh, Iran (the Meshkan triangular structural unit), constitute vast outcrops (up to 250 km 2 ) of high-Mg basaltic andesites to dacites that are associated with high-Nb hawaiites and mugearites. Whole-rock 40 Ar/ 39 Ar ages show a restricted range of 24.1 ± 0.4–22.9 ± 0.5 Ma for the volcanic rocks. The initial ratios of 87 Sr/ 86 Sr and 143 Nd/ 144 Nd vary from 0.703800 to 0.704256 and 0.512681 to 0.512877, respectively, in the high-Mg basaltic andesites–dacites. High-Th contents (up to 11 ppm) and Sr/Y values (27–100) and the isotopic composition of the subalkaline high-Mg basaltic andesites–dacites indicate derivation from a mantle modified by slab and sediment partial melts. Evidence such as reverse zoning and resorbed textures and high Ni and Cr contents in the evolved samples indicate that magma mixing with mafic melts and concurrent fractional crystallization lead to the compositional evolution of this series. The high-Nb hawaiites and mugearites, by contrast, have a sodic alkaline affinity and are silica undersaturated; they are also enriched in Nb (up to 47 ppm) and a wide range of incompatible trace elements, including LILE, LREE, and HFSE. Geochemistry and Sr–Nd isotopic compositions of the high-Nb hawaiites and mugearites suggest derivation from a mantle source affected by lower degrees of slab melts. Post-orogenic slab break-off is suggested to have prompted the asthenospheric upwelling that triggered partial melting in mantle metasomatized by slab-derived melts.